2022
DOI: 10.3390/ma15248883
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of Sol–Gel ZnO:Mg Films and Investigation of Their Structural and Optical Properties

Abstract: This work presents a facile sol–gel method for the deposition of ZnO and ZnO:Mg films. The films are spin coated on silicon and quartz substrates. The impact of magnesium concentrations (0, 0.5, 1, 2 and 3 wt%) and post-annealing treatments (300–600 °C) on the film’s structural, vibrational and optical properties is investigated. Undoped ZnO films crystallize in the wurtzite phase, with crystallite sizes ranging from 9.1 nm (300 °C) to 29.7 nm (600 °C). Mg doping deteriorates the film crystallization and shift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 99 publications
1
1
0
Order By: Relevance
“…Specifically, the bandgap values were determined to be 4.05 eV, 5.11 eV, and 5.24 eV for the compositions (x, y) of (0.25, 0.25), (0.25, 0.50), and (0.50, 0.25), respectively. The findings from experimental research provide confirmation that the bandgap of ternary alloys, specifically BeZnO and MgZnO, and the quaternary alloy BeMgZnO increases as the concentration of Be and Mg atoms incorporated into the ZnO host structure increases [53,[55][56][57][58]. Hence, as depicted in figures 4(a)-(c) and figure 6(a), it can be observed that the bandgap of these alloys exhibits an upward trend as the composition increases.…”
Section: ( ) ( ) = + +supporting
confidence: 58%
See 1 more Smart Citation
“…Specifically, the bandgap values were determined to be 4.05 eV, 5.11 eV, and 5.24 eV for the compositions (x, y) of (0.25, 0.25), (0.25, 0.50), and (0.50, 0.25), respectively. The findings from experimental research provide confirmation that the bandgap of ternary alloys, specifically BeZnO and MgZnO, and the quaternary alloy BeMgZnO increases as the concentration of Be and Mg atoms incorporated into the ZnO host structure increases [53,[55][56][57][58]. Hence, as depicted in figures 4(a)-(c) and figure 6(a), it can be observed that the bandgap of these alloys exhibits an upward trend as the composition increases.…”
Section: ( ) ( ) = + +supporting
confidence: 58%
“…In general, there is a rise in the bandgap values as the composition increases. The recent work of Ivanova [55] showed that the optical bandgap energy of ZnMgO thin films increase from 3.24 to 3.56 eV, and the results clearly reveal that Mg incorporation enlarges the optical bandgap. These results are also confirmed by Siregar [56].…”
Section: ( ) ( ) = + +mentioning
confidence: 86%